2020
DOI: 10.4018/ijhcitp.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on DevOps Capabilities and Areas

Abstract: Businesses today need to respond to customer needs at an unprecedented speed. Driven by this need for speed, many companies are rushing to the DevOps movement. DevOps, the combination of development and operations, is a new way of thinking in the software engineering domain that recently received much attention. Since DevOps has recently been introduced as a new term and novel concept, no common understanding of what it means has yet been achieved. Therefore, the definitions of DevOps often are only a part rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
(236 reference statements)
1
8
0
Order By: Relevance
“…Our research rationale supports and extends the current body of knowledge related to DevOps capabilities such as the work of Teixeira, Pereira, Henriques, Silve, & Faustino [7] who have conducted a systematic review on DevOps capabilities and areas. Furthermore, Badshah, Khan, and Khan [6] have conducted a systematic review on DevOps maturity models and capabilities.…”
Section: Discussion and Research Agendasupporting
confidence: 73%
See 1 more Smart Citation
“…Our research rationale supports and extends the current body of knowledge related to DevOps capabilities such as the work of Teixeira, Pereira, Henriques, Silve, & Faustino [7] who have conducted a systematic review on DevOps capabilities and areas. Furthermore, Badshah, Khan, and Khan [6] have conducted a systematic review on DevOps maturity models and capabilities.…”
Section: Discussion and Research Agendasupporting
confidence: 73%
“…Although other literature reviews on DevOps capabilities have been performed prior to our research [5]- [7], the wider implications of using DevOps in organizations are not yet fully understood and the link between DevOps and firm competitive advantage has been scarcely researched until now. To the best of our knowledge, no theory is available that explains how DevOps teams can deliver strategic value to their organizations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the analyzed studies, it was also observed that DevOps represents: an approach [35,52,55], a cultural movement [17,57], a set of practices [23,27], an emerging paradigm [38,56], a mixture of two words [39], a phenomenon [40], an interdisciplinary theme [22], a set of principles [41], a conceptual framework [42], a development methodology [51], an artificial word [44], a philosophy [47] and a neologism [36]. From the above, it can be evidenced that DevOps has been interpreted in several ways because it is a relatively new subject.…”
Section: Resultsmentioning
confidence: 99%
“…Classification scheme 3.2. Question Q2: What type of research is carried out in the analyzed literature?The studies selected in this research can be divided into two categories: (i) studies with concrete proposals on the adoption of DevOps[17, 23, 40, 44-47, 49, 50, 56] and (ii) systematic reviews of literature[21,27,35,36,42,48,55,57]. Regarding the first category, it was found that 90% of the studies[17, 23, 40, 44-47, 49, 50] registered on the adoption of DevOps use case studies to validate their proposals, these Case studies have been carried out in a range of one to five years in their application depending on the size of the project.…”
mentioning
confidence: 99%
“…Third, while most prior literature review studies reported their results based on the literature published, 77,[84][85][86] our study went beyond by conducting an empirical study and used Fuzzy-AHP approach to prioritize the identified factors. The prioritization-based taxonomy of the identified factors assists the DevOps project managers to revise and improve their project management strategies considering the significance of identified success factors.…”
Section: Study Implicationsmentioning
confidence: 99%